Evaluation of the Final Adult Height and Its Determinants in Patients with Growth Hormone Deficiency: A Single-centre Experience from the South-Eastern Region of Turkey - Meliha Demiral; Edip Unal; Birsen Baysal; Rıza Taner Baran; Hüseyin Demirbilek; Mehmet Nuri Özbek (Galenos Yayincilik, 2020)
Objective:The aim was to determine the final adult height (FAH) achieved by recombinant human growth hormone (rhGH) treatment, the factors affecting FAH and the success of attaining the genetic potential.Methods:Data of 133 patients treated with rhGH therapy were reviewed retrospectively. Patients were grouped according to diagnosis, either isolated GH deficiency (IGHD) or multiple pituitary hormone deficiency (MPHD), and by sex, and pubertal status at the beginning of treatment.Results:The mean age of initiation of treatment was 12.3±2.18 years, and the mean duration of rhGH treatment was 3.65±1.5 years. The mean height standard deviation score (SDS) at diagnosis was -3.11±0.75 SD. All patients received a standardized GH dose of 0.033 mg/kg/day. Mean FAH-SDS was -1.8±0.77 and delta height-SDS (the change in height SDS between the beginning and end of treatment) was 1.28±0.94 SD. FAH-SDS was -1.79±0.86 SD in males; -1.82±0.64 in females (p=0.857); -1.94±0.71 at the beginning of treatment in pubertal patients and -1.68±0.81 in prepubertal patients (p=0.056); -1.84±0.89 in patients with IGHD and -0.47±0.2 in patients with MPHD (p˃0.05). In multiple regression analysis, First year delta height-SDS was the most predictive factor for both FAH-SDS and delta height-SDS.Conclusion:The majority of our patients achieved a final height compatible with their genetic potential as well as population standards when treated with rhGH even having started at a relatively late age. First year delta height-SDS was a predictive factor for FAH.